Double antigen sandwich ELISA for detection of antibodies against Babesia bovis - Primo, María Evangelina (2026)
Babesia bovis is a hemoparasite responsible for bovine babesiosis, an economically important tickborne disease widespread in tropical and subtropical regions of the world. Serological tests are used in calves to evaluate the need for vaccination and the immunity achieved after vaccination. We developed, validated, and evaluated under field conditions a double-antigen sandwich ELISA (dasELISA) using a recombinant major surface antigen 2c (MSA2c) from a pathogenic and an attenuated B. bovis strain. The tests were validated using a panel of 1057 serum samples of known status (217 known-positive and 840 known-negative). Samples from 116 herds (n = 2771) were evaluated by indirect ELISA (iELISA) and dasELISA. Samples with disagreement between ELISAs (231 out of 594, 38.9 %) were analyzed by IFAT. The dasELISA cutoff was ≥ 52 %P, with a diagnostic sensitivity of 94.5 % (95 % CI, 90.5–97.1) and a diagnostic specificity of 96.4 % (95 % CI, 94.9–97.6). The area under the curve (AUC) was assessed to be 0.979, which corresponds to an excellent ability of the assay to discriminate truly infected from truly uninfected animals. Concordance among dasELISA and iELISA was 78.6 %, with a κ value of 0.567 (95 % CI = 0.537–0.598); meanwhile, 57 % and 43 % of the IFAT results agreed with dasELISA and iELISA, respectively. The dasELISA could be useful for large-scale detection of anti–B. bovis antibodies in calves pre- and post-vaccination and for seroepidemiologic investigations, given its appropriate sensitivity and specificity and the simplicity of production.